2022
DOI: 10.1002/adfm.202204686
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Hydrogel‐Based Respiratory Monitoring System for Diagnosing Obstructive Sleep Apnea Syndrome

Abstract: Real‐time monitoring of respiration is vital for human health, especially for forecasting the sleep‐related diseases. A respiratory monitoring system with high accuracy, wearing comfort, portability, and environmental tolerance, is highly desirable, which however remains a big challenge. Here, a multimodal hydrogel sensor with excellent comprehensive performance is fabricated to monitor respiration and diagnose obstructive sleep apnea syndrome (OSAS). The synthetic cellulose‐based hydrogel exhibits good mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…In addition, it can provide robust fluid-tight sealing for a water-filled perforated stomach (diameter: 5 mm) under the condition of continuous water inputs (Figure 6b; Movie S3, Supporting Information). Particularly, this hydrogel also exhibits excellent conductivity of 0.19 S m −1 , which is comparable to reported conductive hydrogels (Figure S6a,b, Supporting Information), [52][53][54] because abundant ions such as quaternary ammonium salt, carboxyl, and sulfonate groups are present within this hydrogel structure. Considering the conductivity and robust adhesive performance of MAH-600, it was explored as a strain sensor for monitoring a beating heart in vivo.…”
Section: Asymmetric Adhesion Characterization Of the Mah-600 Hydrogelsupporting
confidence: 79%
“…In addition, it can provide robust fluid-tight sealing for a water-filled perforated stomach (diameter: 5 mm) under the condition of continuous water inputs (Figure 6b; Movie S3, Supporting Information). Particularly, this hydrogel also exhibits excellent conductivity of 0.19 S m −1 , which is comparable to reported conductive hydrogels (Figure S6a,b, Supporting Information), [52][53][54] because abundant ions such as quaternary ammonium salt, carboxyl, and sulfonate groups are present within this hydrogel structure. Considering the conductivity and robust adhesive performance of MAH-600, it was explored as a strain sensor for monitoring a beating heart in vivo.…”
Section: Asymmetric Adhesion Characterization Of the Mah-600 Hydrogelsupporting
confidence: 79%
“…Copyright 2021, Elsevier. d Obstructive sleep apnea syndrome [ 202 ]. Schematic illustration of cellulose based hydrogel sensor with multimodal sensing capability for monitoring respiration.…”
Section: Health Monitoring Applicationsmentioning
confidence: 99%
“…These smart composite hydrogel sensors, with good flexibility and stretchability, can fit well with the human body and are very suitable for building wearable respiratory monitoring systems. Liu et al [ 202 ] sandwiched a commercial elastomer (VHB 4905, 3 M) between two CH-GT hydrogel layers as a dielectric film to form a multimodal hydrogel sensor (Fig. 12 d).…”
Section: Health Monitoring Applicationsmentioning
confidence: 99%
“…[6,7] In order to well fit the properties of human skin, hydrogels are required to be stretchable, water-rich and most importantly, ion-conductive. Nowadays, hydrogel ionic skins are commonly used in sensors for detecting temperature, [8] strain or stress [9] of human motion. For example, Li et al [2] reported an ionic mimic neuron system for the perception of different signals (pressure and humidity) with dual-modal output.…”
Section: Introductionmentioning
confidence: 99%